2021
DOI: 10.1111/jace.17783
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and design of NaYF4 microprisms via a microwave‐assisted approach for highly sensitive optical thermometry applications

Abstract: Hexagonal NaYF 4 : Er 3+ /Yb 3+ (β-NaYF 4 ) microprisms with uniform particle sizes were synthesized via a microwave-assisted hydrothermal method (MWHM). Nucleation and crystal growth were significantly surpassed owing to the microwave irradiation.Cubic-NaYF 4 : Er 3+ /Yb 3+ (α-NaYF 4 ) nanoparticles were transformed into β-NaYF 4 microprisms with reaction time in between 10 and 120 minutes at 180°C. The shape of the particles was enhanced via controlling the nucleation process with optimized irradiation durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Microwave-aided approaches: Som et al [122] used a microwave-enhanced hydrothermal method to synthesize hexagonal-phase NaYF 4 micro prisms with enhanced UC emission peaks. This method reduces the reaction time and offers uniform morphology, but optimizing parameters and achieving precise control over size is not easy.…”
Section: Pros and Cons Of Nayf 4 Synthesis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microwave-aided approaches: Som et al [122] used a microwave-enhanced hydrothermal method to synthesize hexagonal-phase NaYF 4 micro prisms with enhanced UC emission peaks. This method reduces the reaction time and offers uniform morphology, but optimizing parameters and achieving precise control over size is not easy.…”
Section: Pros and Cons Of Nayf 4 Synthesis Methodsmentioning
confidence: 99%
“…Som et al recently synthesized Microparticles of hexagonal NaYF 4 co-doped with Er 3+ and Yb 3+ using a microwave-enhanced hydrothermal method, resulting in uniform morphology and a pure phase within a shorter reaction time, which is shown in Figure 2. The reaction parameters influenced the phase and morphology, with a notable transformation from cubic to hexagonal phase as the reaction duration increased from 10 minutes to 2 hours at 180 • C. Optimized conditions yielded β-NaYF 4 micro prisms with narrow size distributions and enhanced UC emission peaks at 524 nm, 545 nm, and 659 nm upon 980 nm excitation, attributed to Er 3+ ion transitions [122].…”
Section: Synthesis Of Microscale Nayf 4 Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Photonic glass ceramics (GCs), especially oxyfluoride GCs, combining the advantages of glass (simple fabrication, low loss, tunable optical properties, and high thermochemical stability) 12 and fluoride crystal (low phonon energy), [13][14][15][16] can significantly improve the optical performance of active ions. It has been demonstrated that the weak interaction between photons will deteriorate the optical modulation performance.…”
Section: Introductionmentioning
confidence: 99%